The genome sequence of the Pacific oyster, Magallana gigas (Thunberg, 1793) [version 1; peer review: 2 approved] - Rebekka Uhl; Rob Mrowicki (Wellcome Open Research, 2024)
We present a genome assembly from an individual Magallana gigas (the Pacific oyster; Mollusca; Bivalvia; Ostreida; Ostreidae). The genome sequence is 564.0 megabases in span. Most of the assembly is scaffolded into 10 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 18.23 kilobases in length.